2017
DOI: 10.3390/su9060933
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Research of FDI Spillovers and Financial Development Threshold Effects in Different Regions of China

Abstract: Based on a comprehensive review of previous studies about the threshold effects of financial development on the process of foreign direct investment (FDI) spillovers, the present work roundly measures the financial development from the aspects of scale, structure, and efficiency and applies a multiple threshold regression model to estimate the threshold effects of financial development on FDI spillovers, and then examines the inherent relationship between FDI spillovers effects and the financial development fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…More specifically, the positive HFD–FDI nexus is predominantly driven by the external‐finance and agglomeration effects and is more pronounced for interior and smaller cities. Similarly, Wang and Huifang Liu (2017) examined the relationship between FDI spillovers effects and financial development in different regions of China, using regional panel data from 2000 to 2014. Their results revealed that there are two thresholds of financial development (as proxied by scale, structure and efficiency), existing in the FDI spillover processes in different regions.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the positive HFD–FDI nexus is predominantly driven by the external‐finance and agglomeration effects and is more pronounced for interior and smaller cities. Similarly, Wang and Huifang Liu (2017) examined the relationship between FDI spillovers effects and financial development in different regions of China, using regional panel data from 2000 to 2014. Their results revealed that there are two thresholds of financial development (as proxied by scale, structure and efficiency), existing in the FDI spillover processes in different regions.…”
Section: Introductionmentioning
confidence: 99%
“…Developing economies rely on foreign capital and construct policies to attract FDI (Comes et al 2018). FDI has spillover effects on host economies through human capital, knowledge transfer and competitions in markets (Wang and Liu 2017;Wang et al 2016) and ultimately increases capital stock and stimulates economic growth (Peng et al 2016). FDI can also cause negative effects in spillovers in worse situations (Chou et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These domestic financial reforms enable domestic firms to learn international business strategies to increase their global share and domestically implement this learned environmental friendly business model to achieve long-term sustainable economic growth. After applying the OLS panel technique, Wang and Liu [10] identify that the level of innovation, trade openness, human capital, financial development, and the technological gap can be regarded as the equivalent threshold effects of the sustainable internationalization process. Studies on the internationalization process of Chinese firms indicate that firm-specific advantages like ownership advantages, market-motives, resource-seeking motives, and diversifying motives driving the internationalization process of the country [11,12].…”
Section: Introductionmentioning
confidence: 99%